2004
DOI: 10.1038/oby.2004.19
|View full text |Cite
|
Sign up to set email alerts
|

Restrained Eating Behavior and the Metabolic Response to Dietary Energy Restriction in Women

Abstract: KEIM, NANCY L., AND WILLIAM F. HORN. Restrained eating behavior and the metabolic response to dietary energy restriction in women. Obes Res. 2004;12:141-149. Objective: To determine whether prior eating behavior characterized by dietary restraint alters responses in energy expenditure and substrate oxidation associated with a shortterm, energy-restricted diet. Research Methods and Procedures:A repeated-measures, 3-day diet-intervention study of adequate (125 kJ/kg of body weight) or restricted (62.5 kJ/kg) ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Lower fasting insulin levels have previously been reported in restrained women (112,113) , as well as lower insulin resistance (based on the HOMA model) (112) . However, body weight was found to be a confounder in the latter study (112) , which showed increased fasting insulin sensitivity in restrained eaters.…”
Section: Dietary Restraintmentioning
confidence: 99%
See 4 more Smart Citations
“…Lower fasting insulin levels have previously been reported in restrained women (112,113) , as well as lower insulin resistance (based on the HOMA model) (112) . However, body weight was found to be a confounder in the latter study (112) , which showed increased fasting insulin sensitivity in restrained eaters.…”
Section: Dietary Restraintmentioning
confidence: 99%
“…Another study, however, has shown no significant differences in insulin, glucagon or PP cephalic-phase responses to the sham-feeding of a high-fat or low-fat cake between restrained and unrestrained individuals (119) . Increased levels of fasting TAG (109) and NEFA (83) and lower fasting insulin (112,113) and leptin levels, even after controlling for fat mass (120)(121)(122) , have also been reported in restrained eaters. Moreover, higher levels of cortisol, indicative of increased psychological stress, probably in association with 'eating behaviour', has also been found in some (123,124) but not all studies (111) .…”
Section: Dietary Restraintmentioning
confidence: 99%
See 3 more Smart Citations